Too transparent for signalling? A global analysis of bond issues by property companies - Marc Berninger; Paul Bossong; Dirk Schiereck; Marcel Steinhardt (Accounting & Finance, 2022)
Bond issues often result in negative revaluations of the market value of equity. These market reactions are usually explained by negative signals and asymmetric information about the use of the proceeds. In industries with rather transparent investment opportunities these arguments are not applicable and we expect to find no negative revaluations. Consequently, analysing the stock price reactions to 2299 bond issues by real estate companies between 1996 and 2019, we observe none to positive reactions on the announcement of an upcoming bond issue. The findings underpin the necessity for controlling of industry effects in empirical studies on capital structure decisions.
Keywords: 650; bond issue; capital structure; property companies; REITs; signalling